Qualitative Analysis of Subsurface Water Quality in Challakere Taluk, Karnataka, India - Manjunatha, H; THIRUMALA, S; Aravinda, H B; Puttaiah, E T (Journal of Tropical Life Science, 2012)
Rural India relies mainly on groundwater for drinking and agriculture. Unsustainable withdrawal of groundwater has led to the spectra of depleting the problem of water scarcity. The available groundwater quality is not only contaminated by hazardous pathogenic germs and anthropogenic substances but also geogenic substances is adversely affect the water supply of many regions. The groundwater of Challakere taluk had many threats such as anthropogenic activities, quality deterioration by agricultural activities and over exploitation and also persistence of continuous drought condition. The results of all the findings are discussed in details which reflect the present status of the groundwater quality of the study area. Groundwater is extremely important to the future economy and growth of rural India. If the resource is to remain available as high quality water for future generation it is important to protect from possible contamination. Hence it is recommended that suitable water quality management is essential to avoid any further contamination.Keywords: Groundwater quality analysis, Challakere, Subsurface Water Quality, Karnataka